Attitudes towards faecal immunochemical testing in patients at increased risk of colorectal cancer: an online survey of GPs in England - Von Wagner, C; Stoffel, S; Freeman, M; Laszlo, H; Nicholson, B; Sheringham, J; Szinay, D; Hirst, Y (Royal College of General Practitioners, 2018)
Background There is increasing interest in using quantitative Faecal Immunochemical Test (FIT) to rule-out colorectal cancer (CRC) among patients with high-risk symptoms in primary care. Aim The study aimed to investigate general practitioners’ (GP) attitudes and willingness to use FIT over urgent two-week wait (2WW) referral. Design and Setting A cross-sectional online survey with 1024GPs based in England Method Logistic regression models were used to explore their likelihood of using FIT instead of 2WW, and reported using odds ratios and confidence intervals. Results Just over a third of GPs (n=365) preferred to use FIT as a rule-out test over 2WW. GPs were more willing if they were aged 36-45 (1.59 [1.04-2.43]) and 46-55 (1.99 [1.14-3.47]), thought FIT was highly accurate (1.63 [1.16-2.29]), thought patients will benefit compared to a colonoscopy (2.02 [1.46-2.79]) and were highly confident in discussing the benefits of FIT (2.14 [1.46-3.16]). GPs were less willing if they had had more than 10 urgent referrals in the last year (0.62 [0.40 - 0.94]) and thought that longer consultations will be needed (0.61 [0.44 - 0.83]). Conclusions Our findings suggest that the acceptability of FIT as a rule-out test in primary care is currently low with less than half of GPs who perceived FIT to be accurate preferring it over colonoscopy. Any potential guideline changes recommending FIT in high-risk patients instead of urgent referral to rule-out CRC are likely to require intensive supporting educational outreach to increase GP confidence in the accuracy and application of FIT in this context.